Pengaruh Kompensasi Terhadap Kinerja Karyawan yang di Mediasi Kepuasan Kerja pada PT ISS Cikarang - Suwandi Suwandi; Mahbub Mandahuri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this study is to determine whether there is an effect of compensation on job satisfaction mediated by job satisfaction. The object of research at PT ISS Cikarang. The research was conducted using quantitative methods with SEM Smart PLS software as an analysis tool. The number of samples obtained by using a random sampling technique using the Slovin formula totaled 97 respondents. Data collection was carried out using google form in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects. The results of this study indicate that compensation has an effect on employee performance, compensation has a positive and significant effect on job satisfaction, job satisfaction affects employee performance, job satisfaction is able to provide a positive influence in mediating the relationship between compensation and employee performance in PT ISS Cikarang.